A Review of Botany, Phytochemistry, and Biological Activities of Eight Salvia Species Widespread in Kazakhstan - Yana Levaya; Gayane Atazhanova; Vika Gabe; Karakoz Badekova (Molecules)
The aim of this review is to provide a comprehensive overview of the botany, phytochemistry, and biological activities of eight Salvia species, namely Salvia aethiopis L., S. sclarea L., S. dumetorum Andrz. ex Besser, S. deserta Schang., S. trautvetteri Rgl., S. macrosiphon Boiss., S. virgata Jacq., and S. verticillata L., which are widespread in Kazakhstan. The genus Salvia is renowned for its diverse medicinal properties, and these species are no exception, contributing to the rich natural pharmacopoeia of the region. The botanical characteristics of these species, including their morphological features, distribution, and ecological adaptations, are discussed. The present review also explores the phytochemical composition of these plants, focusing on bioactive compounds such as terpenoids, flavonoids, alkaloids, and phenolic acids, which are responsible for their medicinal potential. Biological activities including antimicrobial, antioxidant, anti-inflammatory, antidiabetic, and neuroprotective effects are evaluated based on available in vitro and in vivo studies. In addition, the review highlights the traditional uses of these species in local medicine and suggests avenues for future research to further elucidate their pharmacological potential. This synthesis provides valuable insights into the medicinal importance of these Salvia species in Kazakhstan and supports their continued exploration for therapeutic applications.